Răspunsuri

2014-04-18T13:44:21+03:00
In triunghiul ADB, mD=90 
triunghiul ABC isoscel⇒AD mediana⇒BD=12√3
                                                        AD=12, aplici Pitagora⇒AB²=BD²+AD²
AB²=144+432=576
AB=24=AC
In triunghiul BEC, m E=90, Pitagora⇒BE²=AC²-EC²
BE²=1728-144
BE=√1584
2014-04-18T14:05:22+03:00
In triunghiul ADB, mD=90 
triunghiul ABC isoscel⇒AD mediana⇒BD=12√3
                                                        AD=12, aplici Pitagora⇒AB²=BD²+AD²
AB²=144+432=576
AB=24=AC
In triunghiul BEC, m E=90, Pitagora⇒BE²=AC²-EC²
BE²=1728-144
BE=√1584